2010
DOI: 10.1016/j.intell.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The mean Southern Italian children IQ is not particularly low: A reply to R. Lynn (2010)

Abstract: Working with data from the PISA study (OECD, 2007), Lynn (2010) has argued that individuals from South Italy average an IQ approximately 10 points lower than individuals from North Italy, and has gone on to put forward a series of conclusions on the relationship between average IQ, latitude, average stature, income, etc. The present paper criticizes these conclusions and the robustness of the data from which Lynn (2010)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
0
25
2
Order By: Relevance
“…The importance of test taking skills and the difficulties that southern Italy students have with group administration of written tests is further supported by the curious observation of Cornoldi et al (2010) that some regional differences currently present in the results of group assessments may disappear if assessment is individual and interactive.…”
Section: The Case Of Apuliamentioning
confidence: 97%
See 2 more Smart Citations
“…The importance of test taking skills and the difficulties that southern Italy students have with group administration of written tests is further supported by the curious observation of Cornoldi et al (2010) that some regional differences currently present in the results of group assessments may disappear if assessment is individual and interactive.…”
Section: The Case Of Apuliamentioning
confidence: 97%
“…Consequently, we have re-examined the mean scores reported by Cornoldi et al (2010) for the reading and mathematics tests administered in groups versus individually. We have transformed them to z-scores based on normative data and then computed the difference in the mean z-score obtained by North and South Italy.…”
Section: The Case Of Apuliamentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars reacted critically to Lynn, both on methodological and historical grounds (Beraldo, 2010;Cornoldi, Giofrè, & Martini, 2013;Cornoldi, Belacchi, Giofrè, Martini, & Tressoldi, 2010;D'Amico, Cardaci, Di Nuovo, & Naglieri, 2012;Daniele & Malanima, 2011a;Felice & Giugliano, 2011;Robinson, Saggino, & Tommasi, 2011). In replying to his critics, Lynn (2010bLynn ( , 2012a provided further evidence of a North-South IQ gap of about 10 points, and showed that Italian regional IQ differences are related to the frequencies of genetic markers for the percentages of North African ancestry in the Southern populations.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The paper proposed that these regional IQs differences explain the long standing problems of the differences in average incomes, literacy, education, stature, infant mortality and the numbers of individuals who have achieved eminence in the arts and sciences incomes, and that they are attributable to immigration from North Africa and the Middle East in the more southerly regions, whose genetic legacy has been to reduce the IQs of the populations. This thesis has been criticised by Beraldo (2010) and by Cornoldi, Belacchi, Giofre, Martini, and Tressoldi (2010), and these criticisms have been answered by Lynn (2010b). Now Felice and Giugliano (2011) have advanced four further criticisms.…”
Section: Introductionmentioning
confidence: 99%